2004
DOI: 10.1213/01.ane.0000103185.18333.68
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effects of Intraarticular Sufentanil and Sufentanil Plus Methylprednisolone After Arthroscopic Knee Surgery

Abstract: The combined use of intraarticular sufentanil (10 microg) and methylprednisolone (40 mg) in arthroscopic meniscectomy surgery reduced both postoperative pain scores and the use of additional analgesics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Kizilkaya et al 80 (level I) reported that administration of sufentanil with methylprednisolone in the knee joint after arthroscopic meniscectomy reduced pain (p < 0.05) and the use of analgesics (p < 0.05) significantly compared with administration of sufentanil alone and reduced it even more com-pared with administration of saline solution (p < 0.05). A similar study conducted by Rasmussen et al 81 (level I) showed that the addition of methylprednisolone to the analgesia regimen further reduced pain, joint swelling, the duration of immobilization, and the need for rescue analgesics (p < 0.05).…”
Section: Orthopaedic and Podiatric Surgerymentioning
confidence: 99%
“…Kizilkaya et al 80 (level I) reported that administration of sufentanil with methylprednisolone in the knee joint after arthroscopic meniscectomy reduced pain (p < 0.05) and the use of analgesics (p < 0.05) significantly compared with administration of sufentanil alone and reduced it even more com-pared with administration of saline solution (p < 0.05). A similar study conducted by Rasmussen et al 81 (level I) showed that the addition of methylprednisolone to the analgesia regimen further reduced pain, joint swelling, the duration of immobilization, and the need for rescue analgesics (p < 0.05).…”
Section: Orthopaedic and Podiatric Surgerymentioning
confidence: 99%
“…Results of studies concerning postoperative analgesic effects of intra-articular administration of opioids are confusing [4][5][6]. Combination therapy by using an opioid plus a non-opioid drug has been proposed for alleviating postoperative pain [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Combination therapy by using an opioid plus a non-opioid drug has been proposed for alleviating postoperative pain [7,8]. Intra-articular glucocorticoid may also improve pain relief after arthroscopy possibly due to its effect on reducing inflammation [6,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Administration after diagnostic arthroscopy or meniscectomy is noted to decrease postoperative pain scores, consumption of analgesics, and recovery time. 14,20,21 The cohort of patients with existing OA undergoing meniscectomy is potentially at higher risk of further joint degeneration and poor symptomatic outcomes, as the relative contribution of OA to the patient's symptoms may exceed that which is due to the meniscal injury. Postoperative corticosteroid injection may alleviate postoperative discomfort and improve the outcomes in this at-risk population.…”
mentioning
confidence: 99%